Stability and Change in Americans' Perception of Freedom. (August 2019) - Patterson, Orlando; Fosse, Ethan
Any American will tell you, this nation's highest ideal is freedom. Survey data teases out how race, income, and political affiliation inflect individuals' sense of lilberty.